The World Anthropological Union (WAU) Congress 2024 - Vesna Vučinić-Nešković (Etnoantropološki Problemi)
The World Anthropological Union (WAU) Congress 2024 “Reimagining Anthropological Knowledge: Perspectives, Practices, and Power”, Johannesburg, South Africa, November 11-15, 2024.